Developmental and hormonal regulation of fiber quality in two natural-colored cotton cultivars - Xiang ZHANG; Da-peng HU; Yuan LI; Yuan CHEN; Eltayib H.M.A. Abidallha; Zhao-di DONG; De-hua CHEN; Lei ZHANG (Journal of Integrative Agriculture, 2017)
Abstract: Cotton cultivars with brown (Xiangcaimian 2), green (Wanmian 39) and white (Sumian 9) fiber were investigated to study fiber developmental characteristics of natural-colored cotton and the effect of hormones on fiber quality at different stages after anthesis. Fiber lengths of both natural-colored cottons were lower than the white-fibered control, with brown-fibered cotton longer than green. Fiber strength, micronaire and maturation of natural-colored cotton were also lower than the control. The shorter fiber of the green cultivar was due to slower growth during 10 to 30 days post-anthesis (DPA). Likewise, the lower fiber strength, micronaire and maturation of natured-colored cotton were also due to slower growth during this pivotal stage. Indole-3-acetic acid (IAA) content at 10 DPA, and abscisic acid (ABA) content at 30 to 40 DPA were lower in the fibers of the natural-colored than that of the white-fibered cotton. After applying 20 mg L−1 gibberellic acid (GA3), the IAA content at 20 DPA in the brown and green-fibered cottons increased by 51.07 and 64.33%, fiber ABA content increased by 38.96 and 24.40%, and fiber length increased by 8.13 and 13.96%, respectively. Fiber strength, micronaire and maturation were also enhanced at boll opening stage. Those results suggest that the level of endogenous hormones affect fiber quality. Application of external hormones can increase hormone content in natural-colored cotton fiber, improving its quality.